Supernova remnant mass accumulated during the star formation history of the z = 3.8 radio galaxies 4c41.17 and TN J2007-1316 - Rocca-Volmerange, B.; Drouart, Guillaume; Breuck, C. (Institute of Physics Publishing, 2015)
In this paper, we show that the supernova remnant (SNR) masses accumulated from core-collapse supernovae (SNe) along the star formation history of two powerful z = 3.8 radio galaxies, 4C41.17 and TN J2007-1316, reach up to , which is comparable to supermassive black hole (SMBH) masses measured from the SDSS sample at similar redshifts. The SNR mass is measured from the already exploded SN mass after subtraction of ejecta while the mass of still luminous stars fits at best the observed spectral energy distribution, continuously extended to the optical-Spitzer-Herschel-submm domains, with the help of the galaxy evolution model Pégase.3. For recent and old stellar populations, SNR masses vary about 10 9-10M☉ and the SNR-to-star mass ratio between 1% and 0.1% is comparable to the observed low-z SMBH-to-star mass ratio. For the template radio galaxy 4C41.17, SNR and stellar population masses estimated from large aperture (>4 arcsec = 30 kpc) observations are compatible, within one order of mass, with the total mass of multiple optical Hubble Space Telescope (700 pc) structures associated with VLA radio emissions, both at 0.1 arcsec. Probing the SNR accretion fueling central black holes is a simple explanation for SMBH growth, which requires the physics of star formation and stellar and galaxy dynamics with consequences for various processes (quenching, mergers, negative feedback) and is also a key to the bulge-SMBH relation.